The Inappropriateness of English for Specific Purposes (ESP) with Learner’s Goals: A Need Analysis on Communication and Islamic Broadcasting Program - Hartina, St.; Syahrir, Syahrir (Universitas Lancang Kuning, 2021)
The course of English for Specific Purposes (ESP) is supposed to prepare students for the professional sector, yet the course at IAIN Palopo in Indonesi is designed in general English without any professional input or assessment of the learner's needs. This research is motivated by the Communication and Islamic Broadcasting program students’ complaints of unsatisfaction with the course since it does not meet their needs. This research aims to examine the English needs of students studying in the communication and Islamic broadcasting program. The researchers used a mixed-methods strategy that incorporates both quantitative and qualitative research. The participants in this study were 60 undergraduates and 30 graduate students. Data was gathered through questionnaires and interviews. The data was then analyzed using the comprehensive concept of need analysis proposed by Dudley-Evans & St. John (1998). The results revealed that the majority of students learn English to help them advance in their careers. Their top priority in ESP is to improve their speaking skills, followed by listening, reading, and writing. Due to the repetitive learning method, inappropriate textbook, and short duration, according to the interview results, the students were also unsatisfied with the present ESP course.